The Role of Religiosity and Financial Factors in Influencing Public Interest in Islamic Home Financing - Putri, Salwa Shafiyya; Athief, Fauzul Hanif Noor (Universitas Muhammadiyah Surakarta, 2025)
This research was conducted because the interest of the Muslim community in sharia-based home financing, namely Islamic Home Financing (IHF), is still low. Although most of Indonesia's population is Muslim and the need to own a home continues to increase, there is still a gap between house prices and people's incomes. In addition, people tend to consider sharia financing more expensive and complicated, so they prefer conventional financing methods. This study aims to analyze how the influence of religiosity and financial factors on the intention of the community in using Islamic Home Financing (IHF) in Indonesia. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The data obtained was 661 respondents who already knew about sharia housing financing. The variables used are Sharia Compliance, Social Influence, Perceived Financial Benefit, Perceived Affordability, Religiosity, and Trust on the intention to use IHF. The results showed that Sharia Compliance, Social Influence, Perceived Financial Benefit, and Trust had a positive and significant influence on the intention to use IHF, while Perceived Affluence and Religiosity did not have a positive and significant effect. These findings show that the community's decision in choosing sharia home financing is based more on the level of trust and suitability of the product with sharia principles, rather than only being influenced by their personal level of religiosity.